Short-term effect of atorvastatin on endothelial function in healthy offspring of parents with Type 2 Diabetes Mellitus - Amudha, K.; Choy, A.M.; Mustafa, Mohd Rais; Lang, C.C. (2008)
Endothelial function is impaired in healthy subjects at risk of type 2 diabetes mellitus (DM). We investigated whether endothelial dysfunction can be normalized by statin therapy in this potentially predisposed population. Flow-mediated dilation (FMD) was measured in 56 ﬁrst-degree relatives (FDRs) (normotensive, normal glucose tolerance) and 20 age-, sex-, and BMI-matched controls with no family history of DM. Other measurements included insulin resistance index using the homeostasis model of insulin resistance (HOMAIR), plasma lipids, and markers of inﬂammation. The FDRs were then randomized and treated with atorvastatin (80 mg) or placebo daily in a 4-week double-blind, placebo-controlled trial. The FDRs had signiﬁcantly impaired FMD (4.4 ± 8.1% vs. 13.0 ± 4.2%; P < 0.001), higher HOMAIR (1.72 ± 1.45 vs. 1.25 ± 0.43; P = 0.002), and elevated levels of plasma markers of inﬂammation—highly sensitive C-reactive protein (hsCRP) (2.6 ± 3.8 mg/L vs. 0.7 ± 1.0 mg/L; P = 0.06), interleukin (IL)-6 (0.07 ± 0.13 ng/mL vs. 0.03 ± 0.01 ng/mL; P < 0.001), and soluble intercellular adhesion molecule (sICAM) (267.7 ± 30.7 ng/mL vs. 238.2 ± 20.4 ng/mL; P < 0.001). FMD improved in the atorvastatin-treated subjects when compared with the placebo-treated subjects (atorvastatin, from 3.7 ± 8.5% to 9.8 ± 7.3%; placebo, from 3.9 ± 5.6% to 4.7 ± 4.2%; P = 0.001). There were also reductions in the levels of IL-6 (0.08 ± 0.02 ng/mL vs. 0.04 ± 0.01 ng/mL; P < 0.001) and hsCRP (3.0 ± 3.9 mg/L vs. 1.0 ± 1.3 mg/L; P = 0.006). Our study suggests that treatment with atorvastatin may improve endothelial function and decrease levels of inﬂammatory markers in FDRs of type 2 DM patients.